Genetic variation in agronomic traits of Erianthus germplasm under multiple‐ratoon crops in Thailand. Issue 4 (14th June 2022) - Terajima, Yoshifumi; Ponragdee, Werapon; Sansayawichai, Taksina; Tippayawat, Amarawan; Chanachai, Sangdaun; Ebina, Masumi; Sugimoto, Akira; Takagi, Hiroko; Hayashi, Hisayoshi
Abstract: Erianthus species have potential as breeding materials for sugarcane and as a biomass crop for fiber production. However, limited information about their genetic variation in agronomic traits hinders their practical utilization. Thus, in this study, we evaluated genetic variation and genetic correlations among 11 agronomic traits in plants grown as multiple‐ratoon crops (plant crop to the third ratoon crop) for 98 clones of E. arundinaceus and 32 clones of E. procerus collected across Thailand. Among the clones tested, large genetic variation was observed in the 4‐yr average, range, and genetic coefficient of variation of dry matter yield for both E. arundinaceus (12.1, 2.2 to 30.6 kg stool −1, and 41.7%, respectively) and E. procerus (8.0, 2.7 to 16.3 kg stool −1, and 25.5%, respectively). Many clones provided better dry matter yield and lower yield reductions in ratoon crops than a sugarcane cultivar ( Saccharum spp. hybrid, 5.2 kg stool −1 ) and Napier grass ( Pennisetum purpureum, 6.6 kg stool −1 ). Genetic variation was observed for stalk number, stalk length, stalk diameter, single stalk weight, Brix, dry matter content, and proportions of both pith and stem parts in stalks, which are important traits in sugarcane breeding. The dry matter yield showed the highest genetic correlation with stalk number (.958 in E. arundinaceus and .700 in E. procerus ). Based on the results, clones with various combinations of advantageous traits were identified as promising genetic resources. These results provide important agronomic information that can be used to exploit this Erianthus germplasm for sugarcane improvement and fiber production in Thailand. Core Ideas: This study evaluated the genetic variation of agronomic traits in 130 Erianthus clones collected across Thailand under multiple‐ratoon crops. Large genetic variation of agronomic traits in Erianthus germplasm showed the importance of germplasm selection for breeding use. Promising genetic resources with advantageous traits for sugarcane improvement and fiber production were identified.